1996
DOI: 10.2172/418424
|View full text |Cite
|
Sign up to set email alerts
|

Advanced hybrid particulate collector. Quarterly technical progress report, April 1--June 30, 1996

Abstract: This report was prepared as an account of work sponsored by an agency of the United States Government. Neither the United States Government nor any agency thereof, nor any of their employees, makes any warranty, express or implied, or assumes any legal liability or responsibility for the accuracy, completeness, or usefulness of any information, apparatus, product, or process disclosed, or represents that its use would not infringe privately owned rights. Reference herein to any specific commercial product, pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2001
2001
2001
2001

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…This result was also encouraging because it showed that the ESP also removed a substantial portion of the fineparticle mass. Precollection of smaller as well as larger particles was desirable because if only [1][2][3] the smaller particles reached the filter, the pressure drop may have been difficult to control.…”
Section: Phase I Summarymentioning
confidence: 99%
See 2 more Smart Citations
“…This result was also encouraging because it showed that the ESP also removed a substantial portion of the fineparticle mass. Precollection of smaller as well as larger particles was desirable because if only [1][2][3] the smaller particles reached the filter, the pressure drop may have been difficult to control.…”
Section: Phase I Summarymentioning
confidence: 99%
“…• Particulate collection efficiencies greater than 99.99% for all particle sizes from 0.01 to [1][2][3][4] 50 µm were achieved.…”
Section: Phase I Summarymentioning
confidence: 99%
See 1 more Smart Citation